Secoergostane- and ergostane-type steroids from Pleurotus cornucopiae var. citrinopileatus. (February 2023) - Kikuchi, Takashi; Anami, Daichi; Morikawa, Shota; Nakagawa, Yuki; Yamada, Takeshi; Li, Wei; Hirano, Tomoya
Abstract: In this study, we described the isolation of an 8, 14-secoergostane-type, a 9, 11-secoergostane-type, and three ergostane-type steroids from the fruiting bodies of Pleurotus cornucopiae var. citrinopileatus . The structure of (22 Z )-3β, 5α, 11-trihydroxy-9, 11-secoergosta-7, 22-diene-6, 9-dione, previously reported, have been revised to (22 E ). Their structures were established using NMR, UV, IR, and mass spectroscopic analyses. Three of the isolated compounds were found to exhibit inhibitory activity on the production of nitric oxide in lipopolysaccharide-stimulated RAW264.7 macrophages with IC50 values of 21.3, 17.6, and 23.1 μM, respectively. Graphical abstract: 8, 14-Secoergostane-, a 9, 11-secoergostane-, and three ergostane-type steroids from the fruiting bodies of Pleurotus cornucopiae var. citrinopileatus . Of these, three compounds exhibit inhibitory activity on the production of nitric oxide. Image 1 Highlights: Five steroids were isolated from Pleurotus cornucopiae var. citrinopileatus. Among them, two compounds were cleaved type steroids. Their structures were established using spectroscopic analyses. Three compounds exhibit inhibitory activity on NO production.